2014
DOI: 10.1590/1519-6984.09513
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and histopathological analysis in South American fish Piaractus mesopotamicus parasitized by monogenean (Dactylogyridae)

Abstract: Monogeneans are the parasites mostly found on the body surface and gills of fish and can cause large losses in farmed fish. Some studies demonstrate elevated parasitic levels causing hematological alterations. But few of them relate the effects of parasitism on the hematology and histopathology of native freshwater farmed fish. This study evaluated the host-parasite relationship in pacu (Piaractus mesopotamicus) parasitized by the monogenean Anacanthorus penilabiatus. Hematological and parasitological assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
14
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 11 publications
9
14
1
3
Order By: Relevance
“…Lizama et al (2007), Tavares-Dias et al (2008), Franceschini et al (2013) and Jerônimo et al (2014) reported the prevalence indexes for A. penilabiatus in P. mesopotamicus in fish farming (P = 81.1%; 76%; 77.3%; 100%, respectively) that were similar to what was reported in this study (P = 97.5%), but higher from the studies of Martins and Romero (1996) and Cohen and Kohn (2009) The monogenoidean species reported in this study was also present in closely related fish species (as shown in Table 4). A. penilabiatus was reported in P. brachypomus, in hybrids P. mesopotamicus x C. macropomum and in P. mesopotamicus x P. brachypomus (Cohen and Kohn, 2009;Tavares-Dias et al, 2008;Franceschini et al, 2003).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Lizama et al (2007), Tavares-Dias et al (2008), Franceschini et al (2013) and Jerônimo et al (2014) reported the prevalence indexes for A. penilabiatus in P. mesopotamicus in fish farming (P = 81.1%; 76%; 77.3%; 100%, respectively) that were similar to what was reported in this study (P = 97.5%), but higher from the studies of Martins and Romero (1996) and Cohen and Kohn (2009) The monogenoidean species reported in this study was also present in closely related fish species (as shown in Table 4). A. penilabiatus was reported in P. brachypomus, in hybrids P. mesopotamicus x C. macropomum and in P. mesopotamicus x P. brachypomus (Cohen and Kohn, 2009;Tavares-Dias et al, 2008;Franceschini et al, 2003).…”
Section: Resultsmentioning
confidence: 96%
“…Some species have detrimental effects on both wild and farmed fish populations, causing important economic damage (Fannes et al 2015). Several authors have studied monogenoideans in P. mesopotamicus: to date, parasitological Eiras et al, 1995;Kohn and Cohen, 1998;Martins et al, 2002a;Pamplona-Basilio et al, 2001;Schalch et al, 2006;Lizama et al, 2007;Kohn, 2005, 2009;Franceschini et al, 2013), histopathological (Martins and Romero, 1996;Campos et al, 2011;Tavares-Dias et al, 2002;Jerônimo et al, 2014), morphological (Boeger et al, 1995;Souza et al, 2000;Cohen and Kohn, 2008;Leão et al, 2015), pathological (Tavares-Dias et al, 2000), hemathological Tavares-Dias et al, 2002 and terapeutic (Martins, 1998;Martins et al, 2000Martins et al, , 2002bTavares-Dias et al, 2002;Onaka et al, 2003;Belo et al, 2005;Schalch et al, 2006;Cruz et al, 2008;Fujimoto et al, 2010;Figueiredo et al, 2011;Carraschi et al, 2014) studies were conducted. The first monogenoidean found in "pacus" was Anacanthorus penilabiatus Boeger, Husack and Martins, 1995, described in the state of São Paulo and posteriorly reported by Martins et al (2000) in the same region.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, infections of the marine fish Lutjanus guttatus with Haliotrema spp. and of the freshwater fish Piaractus mesopotamicus with the monopisthocotylid Anacanthorus penilabiatus (Del Rio-Zaragoza et al, 2010;Jerônimo et al, 2014) are regarded as conditions causing partial damage to the gill filaments, despite the fact that the above authors also found marked haematological changes with elevated percentages of thrombocytes, granulocytes, neutrophils, and eosinophils. In general, the histological picture of Ancyrocephalus infection of the pikeperch showed a pattern very similar to that of Thaparocleidus infection of the sheatfish and Pseudodactylogyrus infection of the eel.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is no surprise that in the intensive cage culture of barramundi (Lates calcarifer Bloch) the first pathogen hampering the propagation of this fish was precisely a monogenean species, Neobenedenia melleni (MacCallum, 1927) (Deveney et al, 2001). Due to the rapid development of marine cage culture systems and the intensive culture of some freshwater species, a whole series of infections caused by different monogenean species has been reported recently (GonzalezLanza et al, 1991;Roubal, 1995;Dezfuli et al, 2007;Sitja-Bobadilla and Alvarez-Pellitero, 2009;Merella et al, 2009;Del Rio-Zaragoza et al, 2010;Yardimci and Pekmezci, 2012;Jerônimo et al, 2014).…”
mentioning
confidence: 99%
“…Proliferative changes in the gill epithelium are among the main disorders observed during the infestation by monogenean (MANSELL et al, 2005;DEL RIO-ZARAGOZA et al, 2010;JERÔNIMO et al, 2014) and can progress to degeneration and necrosis of respiratory tissue, especially in mixed infections with other parasites (YARDIMCI & PEKMEZCI, 2012). The severity of injuries caused by dactylogyrids are directly related to the parasite intensity (DEL RIO-ZARAGOZA et al, 2010).…”
Section: Fish Farm B Pmentioning
confidence: 99%